EARLY CHILDHOOD CHARACTER EDUCATION PRACTICES BASED ON LOCAL WISDOM IN ACEH: CHALLENGES AND EFFORTS MADE IN GLOBALIZATION ERA (GENDER EQUALITY: International Journal of Child and Gender Studies, 2019)
This study was aims to reveal the challenges and efforts in implementing early childhood character education based on local wisdom in Aceh society This study has been conducted using qualitative approach. Its result indicates several challenges faced by Acehnese in implementing character education based on Acehnese local wisdom, including: (a) the impact of technological development; (b) changes in the physical environment such as natural disasters and natural resources; (c) contact with other communities and the culture of the community replaces local culture; (d) modernity promises ease and speed so that the tradition of local wisdom is seen as complicated and slow so that the summarization of tradition is carried out. Therefore, Aceh local wisdom is not only ritual but also contains Islamic values that have become a culture in Aceh.
Keywords: Early Childhood; Character Education; Challenges; Efforts.